Comparison of the Quality of Life in Peritoneal Dialysis and Hemodialysis Patients - I. V. Gribkova (Здоровье мегаполиса)
Chronic kidney disease (CKD) has a profound impact on patients' health-related quality of life (QoL). Particular problems are caused by the end-stage disease, which leads to the need for renal replacement therapy (RRT). Physicians and patients face the challenge of choosing a type of RRT. In this case, it is necessary to take into account not only survival rates but also the quality of life of patients who undergo the therapy, because the ability to function and maintain well-being is one of the treatment goals recommended by the World Health Organization. Therefore, assessing QoL and identifying factors influencing it becomes increasingly important in terms of therapy effectiveness and measures aimed at improving outcomes.The purpose of this work was to review recent scientific studies assessing the quality of life among peritoneal dialysis (PD) and hemodialysis (HD) patients, as well as identifying the better RRT type and risk factors that affect the quality of life. In order to identify the most relevant RRT type, the general questionnaires SF-36 and EQ-5D were used. A search for scientific studies was carried out in the international PubMed/MEDLINE database in April 2024 using the keywords: chronic kidney disease, quality of life, SF-36, EQ-5D, hemodialysis, and peritoneal dialysis. We selected papers published from 2018 to 2024 where the quality of life of patients with CKD re[1]ceiving such RRT types as hemodialysis and peritoneal dialysis was studied.The results showed that PD is more preferable than HD. To achieve a high quality of life, it is also necessary to carefully treat disorders of calcium and phosphate metabolism and anemia, adequately manage concomitant diseases, assist patients with medical care provided at home, organize educational programs to increase patients’ self-efficacy and self-management, and provide psychological assistance if necessary